Trends and Issues in Research on Social Media and Collaborative Learning in PAI Learning from 2018 to 2023: Bibliometric Analysis - Afif Alfiyanto; Dedi Wahyudi; Mailizar; Misbahul Jannah (EduLine: Journal of Education and Learning Innovation, 2023)
This article aims to identify and analyze trends and problems in research on social media and collaborative learning in Islamic Religious Education (PAI) from 2018 to 2023. The author uses a bibliometric study method using Publish or Perish and bibliometric software. The research results show that 1) RQ1: Distribution of Social Media Research and Collaborative Learning in PAI Learning (2018-2023), namely research authority is focused on social media, which is connected to several themes such as Islamic religious education (PAI), and Islamic education. shows that research orientation on social media topics is used in several studies related to PAI learning and Islamic teaching. However, no one has researched the relationship between social media and collaborative learning in PAI learning. So the researcher's orientation in further research needs to be to conduct research on social media in collaborative learning in PAI subjects; 2) RQ2: Network Theme in Social Media Research and Collaborative Learning in PAI Learning, namely the distribution of publication of articles related to "social media" starting in 2019 with one piece, and there is no increase until 2021 which is only 1 article per year, then experienced an increase in 2022 by two articles, and the peak occurred in 2023 with three publications in nationally accredited journals (Sinta). Meanwhile, the publication of articles about "collaborative learning" will only start in 2022 with two pieces. There will be no increase in 2022, which will only be two articles, and in 2023, there will be a significant increase of 5 articles published in nationally accredited journals (Sinta). Meanwhile, publications about "social media and collaborative learning in PAI learning started in 2022 with 1 article and increased in 2023 with two pieces; and 3) RQ3: Authors with the most citations (2018-2023), namely the five best authors with the highest number of citations in the 2018-2023 publication period, namely Susanto & Dwijayanto (27.27%) in 2022, followed by Kambali et al . (18.19%), Lubis et al. (13.63%), and Luthfiyah et al. (13.63%).